The research-policy-deliberation nexus: a case study approach - Camille La Brooy; Margaret Kelaher (BMC, 2017)
Abstract Background Decision-makers tend to make connections with researchers far too late in the game of public policy, expecting to find a retail store in which researchers are busy filling shop-front shelves with a comprehensive set of all possible relevant studies that a decision-maker might some day drop by to purchase. This linear type of relation between research and policy needs to be replaced by a more interactive model that facilitates both researchers obtaining a better understanding of policy processes and policymakers being more aware and involved in the conceptualisation and conduct of research. This paper explores the role of governance in facilitating the research-policy nexus, testing a typology of research utilisation based on Murray's (Soc Policy Society 10(4):459-70, 2011) analysis that considers various degrees of researcher-policymaker deliberation in decision-making processes. The projects were all part of various evaluation efforts carried out by the researchers to explore the use of governance in health promotion activities. Methods Three case studies were chosen to provide some specific examples that illustrate each level of Murray's typology. The examples involve intersectoral health promotion collaborations that combine evidence-based research in health policy initiatives with various levels of researcher involvement. For all three projects, interview data was collated in the same way, coded thematically and analysed to consider the relationship between researchers and policymakers. Results Comparing the three models and their applicability to health promotion interventions, it could be observed that all programmes demonstrated successful examples of research translation. Strong governance imperatives structuring relationships led to more successful outcomes, whereby research was successfully translated into a public policy initiative that also led to improved health outcomes. The key idea across all of these models was that strong governance arrangements mitigated some of the barriers evidenced by the varying degrees of deliberation and researcher involvement in processes. Conclusions The paper demonstrates that successful research utilisation is related to strong governance agendas and that early and ongoing involvement of relevant decision-makers and researchers in the governance processes, that is both the conceptualisation and conduct of a study, tend to be the best predictors of success.